The Phrase “Krivorazbrana Tolerantnost” in Bulgarian Maternity Forum Communication - Bilyana Todorova (East European Journal of Psycholinguistics, 2020)
The aim of the research is to present the meaning and the scope of the phrase “krivorazbrana tolerantnost“ (misunderstood tolerance), which functions as a cliché in everyday communication. The corpus is excerpted from the largest Bulgarian forum platform – bg-mamma and investigates the use of 55 phrases between 2006 and 2017. “Krivorazbrana tolerantnost” is used in public communication to express disagreement with someone’s behaviour/point of view or fear of the changing habits or traditions. Using the cognitive ethnolinguistic approach as well as corpus-based discourse techniques, the paper focuses on the corpus uses of the phrase, its pragmatic influence on the dialogue and the people or the topics which are usually an object of misunderstood tolerance according to bg-mamma forum users. The results show that the context meaning of the phrase usually is over-tolerance or too much permissiveness and it is used in conversations, discussing the rights and liberties of different groups and minorities. As the tolerance itself is a kind of forcing oneself to accept something one does not support or believe in, its meaning and the contextual meaning of the investigated collocation are close.